Advanced zirconia ceramics stabilized with yttria and magnesia: Structure and Vickers microhardness. (October 2022) - Rada, S.; Zhang, J.; Rada, R.; Culea, E.
Abstract: The samples 8YSZ containing 70, 75, 80 mol% ZrO2 and other oxides were prepared by. a high temperature solid state reaction process. Using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and spectroscopic methods were evaluated the effect of oxide addition on the properties of yttria-doped zirconia. X-ray data shows the formation of zirconia (Y-doped), YSZ and/or tetragonal zirconia crystalline phases in all samples. IR data indicate the stretching vibrations of the Si–O bonds from tetrahedral [SiO4 ] units and the stretching vibrations of the Fe–O bonds from [FeO6 ] structural units, respectively. EPR results indicate the destroying of the local ordering of the Fe +3 ion vicinities situated in the rhombic distorted octahedral geometries by the increasing of ZrO2 content in the host ceramic. The highest values of Vickers hardness were recorded for the ceramics containing 70 and 75 mol% ZrO2 . This superior performance can be explained considering the presence of a smaller amount of monoclinic ZrO2 crystalline phase in the ceramic structure. The analysis of the X-ray Absorption Near Edge Structure (XANES) and Extended X-ray Absorption Fine Structure (EXAFS) data shows the presence of Fe +2 and Fe +3 ions. In the ceramics with higher ZrO2 contents the iron atoms adopt a randomly structure due to the highly distorted [FeO6 ] structural units and non-equivalent Fe–O distances in the first coordination shell.